A Simple and Precise Detection of the Adulteration of Olive Oil with Hazelnut Oil Using Lawesson’s Reagent - Demirtas, Ilknur; Ertas, Erdal (Food analytical methods, 2023)
Adulteration of olive oil, particularly with hazelnut oil and/or other less expensive vegetable oils, is among the most encountered ways of defrauding the consumers, which makes the detection of these oils in olive oil an important subject. Off the vegetable oil, the hazelnut oil shows the highest resemblance with olive oil in terms of the lipid profile. Therefore, the profile analysis of the lipidic compounds (fatty acids, sterols, tocopherols, tocotrienols, etc.) using common analytical techniques such as high-performance liquid chromatography and gas chromatography with flame ionization detector does not allow the detection of the hazelnut oil adulteration in olive oil. This study presents a simple and precise method for the detection of hazelnut oil in olive oil through the reaction of Lawesson’s reagent with 5-methylhept-2-en-4-one (filbertone), known as the specific flavor compound in hazelnut oil and does not exist in other vegetable oils. The reaction produces a non-volatile and stable compound that can be identified by high-performance liquid chromatography-ultra violet/visible system with a sensitivity up to 3.0% (w/w). This is a highly satisfactory limit for the detection of adulteration of olive oil to hazelnut oil. Application of the proposed method is not limited with olive oil and can be applied to other oils as well. Graphical Abstract